ANALISIS QUENCHING MATERIAL DISC BRAKE DENGAN VARIASI MEDIA PENDINGIN TERHADAP KEAUSAN SPESIFIK - Gilang Fitra Sanubari; Xander Salahudin; Nani Mulyaningsih (Journal of Mechanical Engineering, 2019)
Disc brakes are part of disc brakes which are generally circular in diameter and usually have small holes as heat release. Braking occurs because of the friction produced between the disc brake and the pad. Therefore, along with the usage time and distance of motorcycle disc brake, the wear will gradually experience wear due to the poor material properties. The purpose of the quenching process is to minimize wear that often occurs with disc brake material with analyze wear values disc brake before and after quenching treatment. This treatment is also solely used to obtain better wear-resistant properties. The wear resistance that can be achieved depends on the carbon content in the steel, the heating temperature, and the cooling media. The method used in this study is quenching at a temperature of 800°C and then held for 15 minutes and cooled using a variety of well water cooling media, salt solution and SAE 20 oil. The stages of the method include: research preparation, equipment and materials needed , testing process, data analysis. From the results of the wear test with a load of 2.12 kg for 60 seconds for each sample the results were obtained salt solutions have an average specific wear value decrease of 0.73 %.